Neuroscientific Perspectives on the Influence of School Emotional Climate on the Development of Social-Emotional Skills in Primary Education - Vasquez, Galo Enrique Vasquez; Ortiz-Delgado, Diana Carolina; Oportus, Ximena Paz Martinez; Morales, Edwar Ferney Roldan; Morales, Edwar Ferney Roldan; Clavijo, Cristina Vilatuna (Journal of Posthumanism, 2025)
The present study explores the interactions between school emotional climate and the development of socio-emotional skills in primary school students from a neuroscientific perspective. It discusses how positive or negative emotional experiences within the school environment can modulate key brain functions related to self-regulation, empathy, and social skills. Through a theoretical review and a qualitative field study in five educational institutions, determinants of the emotional climate and their neuropsychological implications on child learning and well-being are identified. The results highlight the importance of affectively healthy educational environments to optimize brain and emotional development during childhood.